Water and Nutrition : A Framework for Action - Chase, Claire; Bahuguna, Aroha; Chen, Yue; Haque, Sabrina; Schulte, Mik (World Bank, Washington, DC, 2019)
This framework for action was developed to support the inclusion of nutritional considerations in the design of water operations and to help formulate nutrition-enhancing water policy. Chronic undernutrition early in life can cause cognitive and physical impairments that prevent children from achieving their full potential and have lasting consequences on the human capital that is essential for economies of the future to be competitive. The authors present an integrated water and nutrition framework to aid in understanding the various ways that water impacts early child nutrition, drawing on the three dimensions of water security: water quantity, adequate supply of water resources; water quality, water that is free of contamination; and water accessibility, reliable availability to all people, economies, and ecosystems. Each of these in turn affects the underlying drivers of poor nutrition outcomes in children. Challenges associated with water-related conflict and water resources in the context of fragility cuts across each of the drivers of undernutrition. The framework complements guidance notes that describe the evidence of how water sector investments across irrigation, water management, and water supply and sanitation impact early child nutrition and summarize recommendations on how to design interventions for greater impact.